Study of ectopic pregnancy in a tertiary care hospital - Patel, Heny J.; Jani, Shashwat K.; Yadava, Pushpa A.; Vyas, Rupa C.; Asudani, Nitya P.; Rawal, Naisargee G.; Dangar , Kashmira V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ectopic pregnancy, occurring in 1.5-2% of pregnancies globally, is a serious, life-threatening complication and a leading cause of maternal morbidity and mortality in the first trimester. It poses risks to the mother’s life and future fertility by causing potential damage to the fallopian tubes and ovaries. Methods: This retrospective study was conducted at a tertiary care hospital in Ahmedabad, India, from February 2023 to January 2025, involving 40 women diagnosed with ectopic pregnancies. Detailed computerized patient records, including complaints, vital signs, demographics, medical history, and risk factors such as amenorrhea duration, pelvic pathology, surgeries, and infertility treatments, were analyzed. Ultrasound findings, urine pregnancy tests (UPT), and intraoperative observations were also recorded. Data were entered into a pre-structured proforma and analyzed using percentage-based methods. Results: The majority of patients were aged 26-30 years, with 60% in their second pregnancy. Common risk factors included previous ectopic pregnancy (17.5%) and pelvic inflammatory disease (12.5%). Symptoms included amenorrhea (57.5%) and abdominal pain (60%). Among cases, 45% were ruptured tubal pregnancies, and 10% received methotrexate treatment. Conclusions: Ectopic pregnancy should be considered in women of reproductive age with lower abdominal pain, regardless of amenorrhea or sterilization history. Early diagnosis through ultrasound and beta hCG tests is crucial to prevent maternal morbidity and mortality. Timely intervention can reduce complications and significantly improve outcomes.